Isolation and identification of nontuberculous mycobacteria from specimens of lower respiratory tract of transplanted patients based on the evaluation of 16SrRNA gene - Mahdavi, N.; Gholizadeh, P.; Maleki, M. R.; Esfahani, A.; Chavoshi, S. H.; Nikanfar, A.; Sanaat, Z.; Mokhtarzadeh, A.; Nejati, B.; Kafil, H. S. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Nontuberculous mycobacteria are pervasive microorganisms and are often present as saprophytes in humans, animals, and the environment. Today, these bacteria are known as the most important environmental opportunists and, in the last decades, infections by nontuberculous mycobacteria have multiplied, due to increased immunodeficiency (cancer, transplant recipients, HIV).Study design. This study aimed to investigate the infections by nontuberculous mycobacteria in transplanted patients.Methods. The study was performed on 57 samples from respiratory secretions of transplant recipients taken by standard methods. Nontuberculous mycobacteria were identified by culture method and molecular identities of clinical isolates were investigated by PCR amplification using 16SrRNA gene and sequence analysis and Blast of the sequences. Demographic data were evaluated by Spss software.Results. The prevalence of nontuberculous mycobacteria in transplant patients was 22.8%, the age of patients was between 23 and 52 years. The most common involvement of nontuberculous mycobacteria in our transplanted individuals were 6 strains of M avium-intracellulare Complex (42.87%), followed by 2 strains of M marinum (14.29%) and 1 strain each (7.14%) of M xenopi, M chelonae, M intracellulare, M kansasii, M simiae. At the conclusion of the tests, one final strain was identified as M tuberculosis (7.14%).Conclusion. The prevalence of nontuberculous mycobacteria indicates their importance in the fate of these patients. The identification of nontuberculous mycobacteria is a neglected part of microbiology laboratories, due to the lack of sufficient facilities and the risk associated with their culture. Therefore developing routine methods for the identification of these infections appears to be critical, especially in hospitals with the transplantation ward.